Ozonated Air Therapy for the Treatment of Upper and Lower Respiratory Tract Infections as a Potential Therapy for Prevention and Treatment of Covid 19 Infection (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: ozonated air inhalation therapy (OAIT); OAIT for respiratory infections; OAIT for COVID 19